1991
DOI: 10.3168/jds.s0022-0302(91)78206-4
|View full text |Cite
|
Sign up to set email alerts
|

Additive and Nonadditive Genetic Effects on Milk Production in Dairy Cattle: Evidence for Major Individual Heterosis

Abstract: Coefficients for individual and maternal breed composition and the expected contributions of individual and maternal heterosis and breed source of cytoplasm were assigned to 42,554 primiparous Holstein-Friesian, Jersey, and crossbred cows. The individual additive genetic breed effect influenced all milk production traits. Highly significant maternal additive genetic breed effects equivalent to 3% of the mean were identified for milk yield and milk fat percentage. Individual heterosis was highly significant for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 19 publications
6
31
0
2
Order By: Relevance
“…The importance of nonadditive genetic variance in evolution by natural and artificial selection is controversial Crow 2010;Hansen 2013). Nevertheless, numerous studies have found and exploited dominance and epistasis in animal breeding, including dairy (Ahlborn-Breier and Hohenboken 1991;Fuerst and Sölkner 1994;Varona et al 1998;Van Tassell et al 2000;Palucci et al 2007) and beef (Rodriguezalmeida et al 1995) cattle. Diallelic studies have indicated significant SCA for maize grain yield (Doerksen et al 2003;Wardyn et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of nonadditive genetic variance in evolution by natural and artificial selection is controversial Crow 2010;Hansen 2013). Nevertheless, numerous studies have found and exploited dominance and epistasis in animal breeding, including dairy (Ahlborn-Breier and Hohenboken 1991;Fuerst and Sölkner 1994;Varona et al 1998;Van Tassell et al 2000;Palucci et al 2007) and beef (Rodriguezalmeida et al 1995) cattle. Diallelic studies have indicated significant SCA for maize grain yield (Doerksen et al 2003;Wardyn et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the state of Pernambuco, milk production is around 397 million liters (IBGE, 2004), placing the state as the second largest producer in the Northeast region of Brazil. Dairy herds are composed of a large variety of crossed cattle managed extensively, with various studies suggesting the use of crossbred cattle under tropical conditions for milk production (Madgwick and Goddard, 1989;Ahlborn-Breier and Honenboken, 1991;Touchberry, 1992;Zarnecki et al, 1993) yet other studies supporting the use of purebred European cattle in the same regions (Swan and Kinghorn, 1992;Simpson and Conrad, 1993;McDowell et al, 1996). It would appear that the particular environmental conditions may dictate which genetic solution is most appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…This effect had same trend with maternal heterosis in significantly but in milk yield and fat percent traits were negative. Positive heterosis on milk yield were reported by MacDowell & McDaniel (1968), Beckett & Ludwick (1979), Katpatal (1977), Van Der Werf & De Boer (1989), Rincon et al (1982), Ahlborn-Breier & Hohenboken (1991), Kress et al (1996), Rekui (2000), Vanraden & Sanders (2003) but Soldatov & Dutsheev (1991) and Wang et al (1992) reported negative heterosis. Beckett & Ludwick (1979), Rincon et al (1982), Naji (1996) and Rekui (2000) reported positive heterosis on fat yield and MacDowell & McDaniel (1968) and Van Der Werf (1989) reported negative heterosis on fat yield.…”
Section: Resultsmentioning
confidence: 83%
“…Beckett & Ludwick (1979), Rincon et al (1982), Naji (1996) and Rekui (2000) reported positive heterosis on fat yield and MacDowell & McDaniel (1968) and Van Der Werf (1989) reported negative heterosis on fat yield. However Beckett & Ludwick (1979), Rincon et al (1982) and Ahlborn-Breier & Hohenboken (1991) reported negative heterosis on fat percent trait and Rekui (2000) reported positive heterosis. Positive maternal heterosis on milk yield and fat yield traits reported by Kress et al (1996) and Rekui (2000) but Ahlborn-Breier & Hohenboken (1991) and Rekui (2000) reported negative maternal heterosis on fat percent.…”
Section: Resultsmentioning
confidence: 99%